IMPROVING MATHEMATICAL PROBLEM-SOLVING SKILLS THROUGH CREATIVE PROBLEM-SOLVING INSTRUCTION: EVIDENCE FROM A CONTROL AND EXPERIMENTAL GROUP STUDY - Happy Nurina; Zuhri; Hery Saputra (INJOSEDU: International Journal of Social and Education, 2026)
Students’ mathematical problem-solving ability is still at a low level, which is indicated by their difficulty in solving mathematical problems creatively. This condition is closely related to the learning process in the classroom, where conventional teaching methods are still dominantly applied, resulting in students’ learning outcomes not reaching the minimum mastery criteria (KKM). This study aims to examine the effect of the Creative Problem Solving (CPS) learning model as a structured learning approach that emphasizes systematic problem identification, idea generation, and solution development based on students’ creativity to produce effective problem-solving outcomes. This study employed a quasi-experimental research design with a purposive sampling technique. The research population consisted of tenth-grade students at Senior High School 09, located on Jl. Cemara Raya, Padangsari, Banyumanik District, Semarang City, Central Java. The sample involved two classes, namely class X IPA-3 with 35 students as the experimental group and class X IPA-2 with 36 students as the control group. The research instruments included written tests to measure students’ mathematical problem-solving abilities, learning outcome tests, and observation sheets to evaluate the implementation of the learning process. Data were analyzed using descriptive and inferential statistical techniques. The results of data analysis showed that the calculated t-value (t_cal = 4.925) was greater than the t-table value (t_table = 1.666), leading to the rejection of the null hypothesis. These findings indicate that the Creative Problem Solving learning model has a significant effect on students’ mathematical problem-solving abilities.